CORPORATE GOVERNANCE MECHANISMS AND RISK MANAGEMENT PRACTICES IN INDONESIA’S ISLAMIC INSURANCE INDUSTRY - Johar Muammar Khadafi (GREET, 2024)
This study explores the interplay between corporate governance mechanisms and risk management practices in Indonesia’s Islamic insurance (Takaful) industry, which has grown significantly but continues to face challenges related to regulatory complexity and Shariah compliance. Using a qualitative design, the research employed semi-structured interviews, focus group discussions, and document analysis with executives, regulators, and practitioners, analyzed through thematic coding to capture diverse perspectives. The findings indicate that Shariah Supervisory Boards are central to ensuring transparency, accountability, and ethical compliance, with 95% of firms implementing comprehensive governance frameworks aligned with Shariah principles (OJK, 2021). Simultaneously, risk management practices have become more sophisticated, with 80% of companies adopting enterprise risk management systems that integrate financial and non-financial risks (AASI, 2022), while the use of InsurTech tools such as predictive analytics has enhanced efficiency, reduced claim processing time, and improved customer engagement. The study highlights that corporate governance and risk management are mutually reinforcing: effective governance strengthens risk oversight, while comprehensive risk management enhances the credibility of governance structures. Furthermore, OJK regulations have created a more competitive and transparent industry landscape, aligning domestic practices with international standards. This research contributes to the Islamic finance literature by demonstrating how governance and risk practices collectively support institutional resilience and sustainability, while offering critical insights for practitioners, regulators, and policymakers. Future research should investigate the role of emerging technologies such as blockchain, conduct comparative studies with conventional insurers, and examine the integration of corporate social responsibility into Islamic insurance to further strengthen stakeholder trust and align with global sustainability goals.